2003
DOI: 10.1124/mol.63.3.624
|View full text |Cite
|
Sign up to set email alerts
|

Small Ligands Modulating the Activity of Mammalian Adenylyl Cyclases: A Novel Mode of Inhibition by Calmidazolium

Abstract: Molecular cloning of membrane-spanning mammalian adenylyl cyclases (ACs) has led to the discovery of nine different isotypes, making ACs potentially useful therapeutic targets. This study investigated the mechanism by which fungicidal nitroimidazole compounds modulate AC activity. Current evidence indicates that biological control of AC activity occurs through the cytosolic domains. Hence, full-length ACII, ACIX, and recombinant fusion proteins composed of the cytoplasmic loops of human ACIX or the first and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 42 publications
2
26
1
Order By: Relevance
“…Immunostaining of honeybee brain with specific AmAC3 antibodies revealed a prominent expression of AmAC3 in the antennal lobes. When enzymatic activity was inhibited with P-site inhibitors (adenine nucleoside-3 0 -polyphosphates; Dessauer and Gilman, 1997;Haunso et al, 2003) the same rank order of potency was observed for heterologously expressed AmAC3 and ACs present in antennal lobes (2 0 , 5 0 dd3 0 ATP > 3 0 AMP > 2 0 deoxyadenosine). The activity of AmAC3 was also impaired by Ca 2þ /CaM, which was independent of CaM kinase II (CaMKII) activation.…”
Section: Introductionsupporting
confidence: 56%
“…Immunostaining of honeybee brain with specific AmAC3 antibodies revealed a prominent expression of AmAC3 in the antennal lobes. When enzymatic activity was inhibited with P-site inhibitors (adenine nucleoside-3 0 -polyphosphates; Dessauer and Gilman, 1997;Haunso et al, 2003) the same rank order of potency was observed for heterologously expressed AmAC3 and ACs present in antennal lobes (2 0 , 5 0 dd3 0 ATP > 3 0 AMP > 2 0 deoxyadenosine). The activity of AmAC3 was also impaired by Ca 2þ /CaM, which was independent of CaM kinase II (CaMKII) activation.…”
Section: Introductionsupporting
confidence: 56%
“…Preincubation of BEL almost completely blocked the CMZ-induced Ca 2+ rise to 9¡1% DF (pv0.005, n5218/4), which was even significantly smaller than in control cells (pv0.005), in which the re-addition of Ca 2+ induced a Ca 2+ rise of 56¡3% DF (pv0.005, n5154/5, Figure 4A and B). Since CMZ has been reported to inhibit adenylyl cyclase (AC) activity, though at higher concentrations than used in the present study (35), we tested whether the CMZ-induced Ca 2+ influx upon readdition of Ca 2+ can be mimicked by inhibition of AC activity. We used the AC inhibitor SQ 22536 (200 mM) in the absence of CMZ for 15 min before re-adding Ca 2+ .…”
Section: Calmidazolium Induces Ca 2+ Influx Without Store Depletionmentioning
confidence: 97%
“…CMZ has been shown to inhibit the activity of adenylyl cyclase (AC), albeit at greater concentrations than those used in the present study (Haunso et al, 2003). We tested whether the CMZ-induced augmentation of the Ca 2ϩ transient during Ca 2ϩ readdition can be mimicked by the inhibition of AC activity.…”
Section: Camentioning
confidence: 99%